Air-oxidation of phenolic resin aerogels: backbone reorganization, formation of ring-fused pyrylium cations, and the effect on microporous carbons with enhanced surface areas. Issue 81 (2nd November 2017) - Far, Hojat Majedi; Donthula, Suraj; Taghvaee, Tahereh; Saeed, Adnan Malik; Garr, Zachary; Sotiriou-Leventis, Chariklia; Leventis, Nicholas
Abstract : Air-oxidation at 240 °C, followed by pyrolytic carbonization, revealed that carbons from phenolic resins contain fused pyrylium rings and phenoxides. Abstract : This paper is a thorough investigation of the chemical transformations during pyrolytic conversion of phenolic resins to carbons, and reports that all carbons obtained from main-stream phenolic resins including phloroglucinol–formaldehyde (FPOL ), phloroglucinol–terephthalaldehyde (TPOL ), resorcinol–formaldehyde (RF ), and phenol–formaldehyde (PF ) contain fused pyrylium rings and charge-compensating phenoxides. Those four phenolic resins were prepared via a fast HCl-catalyzed process as low-density nanostructured solids classified as aerogels, which, owing to their open porosity, allowed air circulation through their bulk. In that regard, the first step of this study was the air-oxidation of those phenolic resin aerogels at 240 °C. InFPOL andTPOL aerogels, that air-oxidation step kicked off a cascade of reactions leading to ring-fusion aromatization and formation of pyrylium O + -heteroaromatic rings in every repeat unit of the polymeric backbone. Despite the complexity of the process, those structural forms were well-defined, and were retained through pyrolytic carbonization (800 °C). Under the same conditions (240 °C/air), RF andPF aerogels did not undergo aromatization; instead, they just went through an autooxidation-like process that converted the –CH2 – bridges between phenolic moieties into carbonyls (CO). Importantly, however, upon further stepwise pyrolysis under Ar, by 600 °C all four systems (TPOL, FPOL, RF andPF ), irrespective of whether they had been previously oxidized or not, converged to a common chemical composition. Thereby, carbon produced by pyrolysis of phenolic resins at 800 °C always contains fused pyrylium rings. All chemical analysis relied on FTIR, solid-state 13 C NMR, XPS and CHN analysis. The only and significant difference made by the low-temperature (240 °C) air-oxidation step was identified with the surface areas of carbons from aromatizable systems (TPOL andFPOL ), which were higher than those from direct pyrolysis of as-prepared aerogels. Upon further reactive etching with CO2, those surface areas went as high as 2778 ± 209 m 2 g −1 . Those findings are directly relevant to high surface area carbons for gas sorption ( e.g., capture and sequestration of CO2 ) and ion exchange materials.